(untitled) (Research, Society and Development, 2022)
Depression is considered a public health problem and is one of the main causes of professional or social disability worldwide. Antioxidants are substances known for their preventive or therapeutic effects on various diseases, including depression. These benefits can be explained by the inherent ability of these molecules to modulate cell signaling pathways. This study aimed to evaluate the neuroprotective effects of resveratrol in an in vitro model of depression. Experimental studies were performed with U-87 MG glial cells derived from the human brain lineage. Different concentrations of resveratrol were used in the presence or absence of kynurenine, a metabolite of the amino acid tryptophan necessary for the synthesis of serotonin. Cell viability was evaluated by determining the ability of cells to reduce the MTT compound (3-[4,5-dimethylthiazol 2-yl]-2,5-diphenyltetrazoline bromide), in addition to cell morphological evaluation. To assess the level of oxidative stress, treated glial cells were subjected to the TBARS test to quantify lipid peroxidation. Kynurenine doses of 100 and 200 µM were cytotoxic, reducing glial cell viability and altering cell morphology. This reduction was accompanied by increased oxidative damage to lipids. Resveratrol (10 µM) was shown to be preventive in maintaining the viability of glial cells when treated with 100 µM kynurenine. The results may contribute to the understanding of the mechanisms involved in depression, contributing to the new focus on the ability of polyphenols, compounds naturally found in the diet, to become adjuvant therapeutic agents for the treatment of neuropsychiatric disorders.